Purified high-sulfur coal as a fuel for direct carbon solid oxide fuel cells - Jiao, Y.; Xue, X.; An, W.; Julião, P.; Wang, Wei; Yang, G.; Zhou, W.; Li, S. (John Wiley & Sons Ltd., 2018)
© 2018 John Wiley & Sons, Ltd. The use of low-rank coal in a clean and efficient manner is a major challenge facing the current coal technology. A high-sulfur coal with 4.5 wt% sulfur is chosen to examine the compatibility of the pristine coal and the purified contrast with a solid oxide fuel cell (SOFC) with nickel cermet anodes. Desulfurization of the pristine coal is performed by molten caustic leaching method with a removal ratio of 80%. Analyses of the physicochemical properties of coal samples indicate that the purified coal has a more favorable structure and higher Boudouard reactivity, which is suitable as a fuel for fuel cells. The assessment of electrochemical performance reveals that the purification treatment not only makes the peak power density of SOFCs improve from 115 to 221 mW cm -2 at 900°C but also extends their durability from 1.7 to 11.2 hours under a current density of 50 mA cm -2 at 850°C with a fuel availability increasing from 6.25% to 40%. The postmortem analyses show that far less deposited carbon and nickel sulfide are observed on the anode surface. The fuel-based investigation reveals that the purified coal is a promising fuel for direct carbon fuel cells.